M. Andreas Gnospius Gedani Ad S.S.Trinitatis Aedem V.D.M. Natus MDCXXXIII D. XVI Iun. Denatus MDCCII D. XXVI Iun. / Joh. Chr. Böcklin. - Böcklin, Johann Christoph (1657-1709) (1702)
Przedstawia portret w popiersiu Andreasa Gnospiusa (1633-1702).